Is ethics a central element to business education? A qualitative case study in a MBA’s programme - Silva, M. Gabriela (15th EBES Conference - Lisbon, 2015)
This study highlights the importance of ethics as a core factor for educating students in business schools. Specifically, it aims to shed light on issues related to group-based activities in a MBA course when the emphasis on complex social and human factors remains, for the most part, unspoken. A qualitative approach, based on 60 critical incident technique interviews with MBA students, was undertaken. Findings reveal that students did not have many clues about how people should relate to each other in group constellations. Consequently, they normally experienced struggles, tensions and conflicts when they performed group-based activities. Furthermore, when students addressed themselves to the meaning of their group experiences, they often uncovered that the course of a group life is a social construction, and so the important thing is to build a working group. Outcomes such as this emphasize the view that knowledge and skills on group functioning and processes can be acquired through an experiential learning activity. But, more significantly, they call for institutional ethics and, in turn, to restore balance to the curriculum, in order to link hard and soft skills, and the interests of different stakeholders.